2014
DOI: 10.4141/cjps2013-095
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield of simple and complex grass–legume mixtures under two management strategies

Abstract: Foster, A., Vera, C. L., Malhi, S. S. and Clarke, F. R. 2014. Forage yield of simple and complex grass–legume mixtures under two management strategies. Can. J. Plant Sci. 94: 41–50. Limited information is available on the dry matter production, protein content and species composition of complex mixtures of introduced perennial forage crop species for hay and pasture in the moister regions of Saskatchewan. A field experiment was sown on 2008 May 27 at Melfort, Saskatchewan, Canada, on a thick Black Chernozem (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…One of main qualities of these forages crops (grasspea and red vetchling) consist of its high protein content (Polignano, 2007). The results of this study, show higher protein content than observed by Foster et al (2014) and similar than Van Saun (2016) results. This is because, there were selected for this study various forage legumes varieties which generally produce high quality forage.…”
Section: Crude Protein Contentsupporting
confidence: 88%
“…One of main qualities of these forages crops (grasspea and red vetchling) consist of its high protein content (Polignano, 2007). The results of this study, show higher protein content than observed by Foster et al (2014) and similar than Van Saun (2016) results. This is because, there were selected for this study various forage legumes varieties which generally produce high quality forage.…”
Section: Crude Protein Contentsupporting
confidence: 88%
“…They also indicated no advantage to a 3-harvest over a 2-harvest system for total annual forage production and no advantage of a single-harvest system over multiple-harvest systems for stand vigor and persistence when the first harvest was post-anthesis (i.e., during early July). In Saskatchewan, Canada a 2-cut system, with the first cut at full anthesis in mid-July, was more productive than a 3-cut system, with first cut at pre-anthesis in midJune, for smooth bromegrass on unfertilized soil [17]. Levels of forage production attained in this study are comparable to those reported for smooth bromegrass for a 5-yr study in Minnesota [18] and a 3-yr study in northeastern Nebraska [19].…”
Section: Forage Productionsupporting
confidence: 74%
“…The similar P concentration among the grass monocultures and mixed forage systems can be attributed to the dramatic decline in the legume component from 18% in 2017 to 0.5% in 2018. This may be attributed to the two-cut harvest system utilized in this study, instead of a greater frequency of harvest of grass-legume mixtures [68]. Unlike the lack of difference in P concentration between the two tall fescue cultivars, Bélanger et al [67] reported differences in tissue P concentration among genotypes of timothy (Phleum pratense L.).…”
Section: Forage Tissue Phosphorus Concentrationmentioning
confidence: 66%